2020
DOI: 10.1139/cjm-2019-0493
|View full text |Cite
|
Sign up to set email alerts
|

FtsA G50E mutant suppresses the essential requirement for FtsK during bacterial cell division in Escherichia coli

Abstract: In Escherichia coli, the N-terminal domain of the essential protein FtsK (FtsKN) is proposed to modulate septum formation through the formation of dynamic and essential protein interactions with both the Z-ring and late-stage division machinery. Using genomic mutagenesis, complementation analysis, and in vitro pull-down assays, we aimed to identify protein interaction partners of FtsK essential to its function during division. Here, we identified the cytoplasmic Z-ring membrane anchoring protein FtsA as a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…E. coli RlpA lacks LT activity (due to the substitution of the catalytic aspartate with a serine) and is bound to the large (1329 amino acids), polytopic membrane protein FtsK of the divisome 38 , 59 . FtsK coordinates the essential function of chromosome segregation with cell division, and in this task, may structurally connect the cytoskeletal proteins to proteins of the divisome located in the periplasm, including the membrane-bound PBPs 60 , 61 . Deletion of RlpA from E. coli does not, however, give a recognizable phenotype 49 .…”
Section: Introductionmentioning
confidence: 99%
“…E. coli RlpA lacks LT activity (due to the substitution of the catalytic aspartate with a serine) and is bound to the large (1329 amino acids), polytopic membrane protein FtsK of the divisome 38 , 59 . FtsK coordinates the essential function of chromosome segregation with cell division, and in this task, may structurally connect the cytoskeletal proteins to proteins of the divisome located in the periplasm, including the membrane-bound PBPs 60 , 61 . Deletion of RlpA from E. coli does not, however, give a recognizable phenotype 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that several mutations in FtsA bypassed the requirement of a number of essential cell division proteins in E. coli , including ZipA (30), FtsK (31), and FtsN (32). Among these, FtsA R286W (FtsA*) was the first gain-of-function mutation found in E. coli , which allowed the survival of mutants lacking ZipA (Δ zipA ) or FtsK (Δ ftsK ) (30, 31, 33). Additionally, FtsA I143L (34) and FtsA E124A (32) weakly bypassed the requirement of FtsN.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its important role in DNA segregation and cytokinesis FtsK mutations have severe phenotypes. In E. coli a loss of FtsK can be compensated by a suppressor mutation in FtsA (51). Although our Tn-Seq screen identified several transposon insertions into the FtsK gene in wild type background, we were unable to construct a clean deletion of the gene.…”
Section: Discussionmentioning
confidence: 99%